Digital replicas and democracy: issues raised by the Hollywood actors’ strike - Asuka Yamazaki (Humanities & Social Sciences Communications)
Abstract Recent years have seen artificial intelligence (AI) technologies from large companies increasingly privatize people’s data, creating asymmetrical and undemocratic economic relations. Specifically, generative AI disseminates false information, distorts perceptions, and transforms the free and critical cultural public sphere into one that is privatized and undemocratic. This study examines the major Screen Actors Guild-American Federation of Television and Radio Artists strike in Hollywood in May 2023, focusing on the issues raised against actors’ digital replicas from a democratic perspective. The introduction of this technology, aiming to enhance the audience’s immersive experience, reinforces the cultural imperialistic and neoliberal hierarchical relation between companies and actors. Moreover, this study explains how digital replicas relegate actors to a subjugated state, damage their image, and demote them to the periphery of filmmaking, thereby resulting in undemocratic problems that deprive them of their subjectivity and creativity. The main findings are as follows: (1) Actors’ data, embedded in the data capitalism structure, are used to generate their digital replicas, thus causing economic and structural inequalities. Video companies’ monopolization and unapproved use of such data lead to the loss of these actors’ freedom and humanity. (2) Unauthorized digital replicas of actors through deepfakes globally damage their public image and social authority, and such false body representation has negative cultural and ontological effects on them. (3) The use of digital replicas excludes actors from the filmmaking process, eliminating their interaction and creativity in relation to other creators and audiences and preventing their participation in the critical and cultural public sphere of cinema. As humans and generative AI continue to coexist, using digital replicas with actors’ legal consent is important as it ensures their independence and expressive potential. This will develop a democratic film industry that enhances the interactive cinema–media cultural public sphere.